Pricing Pollution - Torben K. Mideksa (Center for Economic Studies and ifo Institute (CESifo), 2020)
I examine a policy-making game among countries that must choose both a policy instrument (e.g., a tax or a quota) and its intensity (i.e., the tax rate or the quota level) to price pollution. When countries price pollution non-cooperatively, they not only set the intensity inefficiently, they are also likely to adopt Pigouvian fees, despite quotas being better from a welfare perspective. Adopting a Pigouvian fee to address a multi-country externality generates a risk externality, and non-cooperatively chosen quotas can generate higher social welfare than maximum social welfare Pigouvian fees can deliver.
Keywords: C72; D81; F50; H21; Q38; Q58; 330; environmental policy; global pollution; international relations